Discovery Of Antibacterial-Producing Actinobacteria From Selected Malaysian Mangrove Sediments - Awang, Mohd Syafiq (2018)
The rapid emergence of multi-drug resistant pathogenic bacteria has called for intensive research on the discovery of new and potent antibacterial metabolites. Actinobacteria is one of the major producers of antibacterial secondary metabolites. Among the most reliable sources for the isolation of actinobacteria are forest soil and marine sediments. Mangrove is a rich marine environment, but it is seldom explored for actinobacterial isolation. Accordingly, the present study was carried out with the main aim to isolate and screen for potential antibacterial-producing actinobacteria from mangrove sediments. The mangrove sediments were sampled from the mangrove environment located at Balik Pulau, Pulau Pinang, Malaysia. A total of 131 actinobacterial isolates were successfully isolated by using a combination of selective pre-treatment and isolation media. Preliminary screening of these isolates against five species of Gram-positive and Gram-negative bacteria using cross streak plate method showed that 54 % of the isolates were capable of producing antibacterial metabolites. Among these active isolates, 70 % have broad-spectrum antibacterial activity against both Gram-positive and Gram-negative test bacteria, 24 % have narrow-spectrum antibacterial activity against only Gram-positive bacteria and 6 % against only Gram-negative test bacteria. Five actinobacterial isolates with potent broad-spectrum antibacterial activity were selected for cultivation in three litres submerged culture fermentation using a bubble-column bioreactor.